Implementasi Ekonomi Kreatif Dan Kewirausahaan Dalam Mewujudkan Mahasiswa Berjiwa Enterpreneur - Noviansyah Noviansyah; Dyah Ayu Putriani; Tati Herlina; Astrina Utami; Ahmad Dani (Universitas Muhammadiyah Manado, 2021)
This Community Service program aims to instill the values of entrepreneurship and creative economy in order to foster an entrepreneurial mindset among students of the Faculty of Economics and Business, University of Baturaja. Through counseling, training, and entrepreneurship bazaar activities, students received both theoretical knowledge and practical experience in developing creativity-based business potential. The results of the program showed an increase in students’ motivation, understanding, and enthusiasm in running independent businesses. The activity also demonstrated that participatory and applicative approaches in entrepreneurship education can bring about changes in attitude and encourage the development of an entrepreneurial mindset focused on innovation and economic empowerment. Therefore, this program positively contributes to strengthening students' entrepreneurial capacity through community service activities.